Penerapan Etika Bisnis Islam pada Pedagang Batik di Pasar Grosir Batik Setono Pekalongan - Rahman, Miftahur; Daswan, Lestari; Idris, Munadi (Robust: Research of Business and Economics Studies, 2022)
The research explores the understanding and implementation of Islamic business ethics among batik traders in the Setono Batik Wholesale Market. Employing a qualitative approach, the study combines normative theological, sociological, and phenomenological perspectives to collect data from primary sources (traders and buyers) and secondary sources (relevant literature). The findings reveal that while most traders in the market comprehend Islamic business ethics inspired by the Prophet Muhammad's trading practices, some remain unaware of these ethical principles, especially those with lower education levels. The study shows that the principles of Islamic business ethics, encompassing qualities like honesty, trustworthiness, transparency, and spreading good, are predominantly embraced by traders, although a few still prioritize profit-seeking over the pursuit of blessings and a favorable afterlife in their business dealings.